Synthesis, Anti-enzymatic Appraisal, In Silico, and SAR Analysis of 5-Aryl/Heteroaryl-2,2-dimethyl-1,3-dioxane-4,6-dione Derivatives - Khatoon, Saira; Mehfooz, Haroon; Shehzadi, Syeda Aaliya; Saeed, Aamer; Kalsoom, Saima; Channar, Pervaiz Ali; Ismail, Hammad (Wiley-V C H Verlag Gmbh, 2025)
A sequence of new 5-aryl/heteroaryl-2,2-dimethyl-1,3-dioxane-4,6-dione derivatives were synthesized by condensing Meldrum's acid and triethyl orthoformate with differently substituted aromatic and heteroaromatic amines in good to excellent yields. The chemical structures were characterized by spectroscopic techniques and the synthesized entities were evaluated for chymotrypsin and urease inhibition. Interestingly, among the synthesized derivatives, compound containing 5-nitropyridin-2-yl ring exhibited dual inhibition activities with IC50 value (8.67 +/- 0.1) close to the control (Chymostatin:8.24 +/- 0.11) against chymotrypsin; and (29.21 +/- 0.98) close to the control (Thiourea:21.25 +/- 0.15) urease in mu M concentration. Further, molecular docking analysis was performed on the 3D crystal structure of Jack bean urease protein and a serine proteinase alpha-chymotrypsin with synthesized ligands, to observe the binding interactions. All the synthesized compounds docked well into the active sites of the proteins, the most active compound showed H-bonding interaction with amino acid HIS A 594 residue through carbonyl oxygen of dioxane ring and CME A 592 through oxygen of nitro group against 3La4 urease protein, while against chymotrypsin, it revealed the hydrogen bonding between amino acids: SER C 217, GLY C 216, and SER C 190. The role of pharmacophore was evaluated using the diverse substituents on aromatic/heteroaromatic rings, and on the basis of that SAR was developed.
Keywords: Chymotrypsin Inhibitors; Meldrum's Acid; Molecular Docking; Sar; Urease Inhibitors